Graphology as a Linguistic Level of Analysis: Definition, Theoretical Background and Proposals for Categorization - Gómez-Jiménez, Eva (Miscelánea: A Journal of English and American Studies, 2015)
The present paper aims at presenting some fundamental ideas that clarify the concept of graphology as a linguistic level of analysis. Departing from the lack of a theoretical apparatus at this level, this article explains what graphology means, what has been previously published on this matter and how this can be categorized into different sub-levels of study according to Levenston (1992) and Lennard (2005). This paper takes for granted Firth’s (1957) belief that all branches of linguistics are concerned with meaning; and that graphology should therefore receive due attention from linguists as all the other linguistic levels (i.e. lexis, grammar or phonology) have. The results of this research indicate that graphology as a system has been neglected both in theoretical and in practical terms. Further work in this field is therefore needed in order to facilitate the analysis of visual elements in literary and non-literary texts.